Effect of ensiling whole crop oat with lucerne in different ratios on fermentation quality, aerobic stability and in vitro digestibility on the Tibetan plateau. Issue 5 (20th October 2016) - Chen, L.; Guo, G.; Yuan, X. J.; Zhang, J.; Wen, A. Y.; Sun, X. H.; Shao, T.
Summary: The objective of this study was to determine the effect of ensiling different ratios of whole crop oat to lucerne on fermentation quality, aerobic stability and in vitro digestibility of silage on the Tibetan plateau. Four experimental treatments were produced varying in the ratio of forages on a fresh matter (FM) basis: 1) 100% oat (control, dry matter (DM) content: 317 g/kg), 2) 90% oat + 10% lucerne (OL10, DM content: 316 g/kg), 3) 80% oat+ 20% lucerne (OL20, DM content: 317 g/kg) and 4) 70% oat+ 30% lucerne (OL30, DM content: 318 g/kg). All treatments were packed into laboratory‐scale silos and ensiled for 60 days and then subjected to an aerobic stability test for 15 days. Further, the four experimental treatments were incubated in vitro with buffered rumen fluid to study the nutrient digestibility. All silages were well preserved with low pH and NH3 ‐N contents, and high lactic acid contents and V ‐scores (evaluation of silage quality). Increasing the lucerne proportion increased (p < 0.05) crude protein (CP) content of silage, whereas neutral (NDF) and acid (ADF) detergent fibre contents were not affected. Under aerobic conditions, the control silage showed higher (p < 0.05) yeast counts (>10 5  cfu/g FM) followed by OL10 silage, and OL10 silage improved aerobic stability for 74 h. OL20 and OL30 silages showed fewer (p < 0.05) yeasts (<10 5  cfu/g FM) and markedly (p < 0.05) improved the aerobic stability (>360 h). After 48‐h incubation, OL30 silage increased (p < 0.05) in vitro dry matter digestibility (IVDMD) and neutral detergent fibre digestibility (IVNDFD) compared with the control silage. These results suggest that replacing oat with lucerne had no unfavourable effects on fermentation quality of silage, but improved CP content, aerobic stability IVDMD and IVNDFD. OL30 silage was the best among the three mixed silages.